Non-clinical factors and predictors of self-ratings of oral health among young adolescents in a rural Nigerian population - Folake B. Lawal; Mumini A. Dauda (Universidade Estadual de Campinas, 2018)
Aim: The aim of the study was to assess the non-clinical determinants and predictors of self-ratings of oral health among young adolescents in a Nigerian rural population. Methods: A cross-sectional survey was conducted among adolescents of 11-13 years old in Igboora, Nigeria. Information on self-rating of oral health, self-assessed satisfaction with oral health condition and tooth appearance, pain history, consultation with the dentist and oral hygiene measures were obtained using structured questionnaires translated to the local language. Data were analysed using SPSS version 23; Chi Square and logistic regression were used to establish associations between variables and predictors with p value < 0.05 statistically significant. Results: A total of 400 respondents participated in the study. Most 346 (86.5%) rated their oral health positively. Those who expressed dissatisfaction with the appearance of their teeth, 17 (44.7%) dissatisfaction with their oral health condition, 25 (45.5%) had toothache in the preceding six months, 44 (19.7%) perceived a need for dental treatment, 43 (16.7%) or cleaned their teeth once daily or less frequently, 37 (20.9%), rated their oral health poorly (p < 0.001, p < 0.001, p = 0.001, p = 0.012, p < 0.001, respectively). The significant predictors of self-ratings of oral health were self-assessed satisfaction with oral health condition, toothache in the preceding six months and frequency of tooth cleaning. Conclusion: Satisfaction with oral health condition, toothache in the preceding six months and frequency of tooth cleaning are factors that predict self-rating of oral health in young adolescents in the rural community studied.